2022
DOI: 10.3389/fmars.2022.812911
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Variability of the Kuroshio Shelf Intrusion and Its Relationship to Upper-Ocean Current and Temperature Variability in the East China Sea

Abstract: The strong variability of the Kuroshio northeast of Taiwan is associated with changes in the strength of the Kuroshio shelf intrusion (KSI) in the East China Sea (ECS), which is a westward shift in the Kuroshio toward the shelf region. The KSI contributes to the exchange of different water masses between the shelf and the western boundary current regions, and plays a key role in ecosystem and climate regulation in the ECS and the downstream East Asian Marginal Seas. This study investigates the long-term variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…S. dumerili prefers a low water current (Figure 4) which may be the reason why observed catch rates did not match. Many studies have reported that the Kuroshio Current, which flows close to the coastal area near the northeastern part of Taiwan [47][48][49].…”
Section: Predicted Spatial Distribution Pattern Of the Greater Amberjackmentioning
confidence: 99%
“…S. dumerili prefers a low water current (Figure 4) which may be the reason why observed catch rates did not match. Many studies have reported that the Kuroshio Current, which flows close to the coastal area near the northeastern part of Taiwan [47][48][49].…”
Section: Predicted Spatial Distribution Pattern Of the Greater Amberjackmentioning
confidence: 99%
“…Wang and Oey (2014) indicated that the strengthened northeast wind would significantly enhance the KI. Recently, Kang and Na (2022) further reported significant correlation relationships between KI and wind stress and wind stress curl. Does this mean stronger northeast winds will generate stronger KI, and thus leads to a stronger ZFCF?…”
Section: Role Of Background Currentsmentioning
confidence: 91%
“…As the major channel connecting the Yangtze River and the ECS, the Yangtze River Estuary is influenced by strongly varying river discharges and moderate tides (Yun, 2004). In addition, the Kuroshio is a western boundary current in the North Pacific that flows northeastward after entering the southeast ECS (Kang and Na, 2022). It has significant effects on both the physical and biological processes of the North Pacific, including nutrient and sediment transport, regional climate, and Pacific mode water formation (Hu et al, 2015;Das et al, 2021).…”
Section: Study Areamentioning
confidence: 99%